O gesto na clínica fonoaudiológica: um estudo sob o olhar da análise discursiva materialista - Kitahara, Michelle Fogaça de Oliveira (2018)
Gesture has been exhaustively mentioned in the international scientific literature under different approaches and therapeutic methods. This dissertation aims to investigate the gesture in the speech pathologists’ clinics together with the dominant ideology on the light of the theory and methodology known as Materialist Discourse Analysis. Twelve speech therapists that work in different clinical areas were interviewed in search of the main discursive thread that support their discourse. The semi-open interviews were recorded and the discursive data transcribed. Fragments were extracted and analyzed from the perspective pointed out above. The analysis reveals that the conducting thread of the therapists’ discourse is the positivist ideology of Science, which fragments the subjects, body and language, allocating speech and gesture in a hierarchy system where gesture is subordinated to the former. The language materiality reveals an unconscious identification of the therapists with the significant “Fono-Speech, Audio-Audio, Logia-Study” (Speech Therapist) since the return of speech and their professional identity is brought up. The deaf perspective approach appears to be related to the discourse about gesture, where LIBRAS (Brazilian Sign Language), as a codified way of language was considered a threat to the speech statute. It was also observed a broader meaning of the term speech, different from those only related to the articulation of sounds to that one affecting the others through the language of hands/gestures. Under such perspective, there are also formations that challenge the dominant ideology welcoming gesture as an important tool in the clinics, in the evaluation and treatment. Collected data was also supplemented with literature review of the last 10 years using the key-words gesture/s in the main Brazilian speech pathologist journals. 23 articles have been found where the majority refers to gesture in the context of clinical care of aphasic patients, autistic and other specific syndromes beyond the understanding of the language acquisition process